The laboratory-assessed performance predictors of elite cross-country marathon mountain bikers - Crivoi do Carmo, E.; Barroso, R.; do Prado, D. M. .; Inoue, A.; Machado, T.; Cal Abad, C. C.; Loturco, I.; Tricoli, V. (Kinesiology, 2021)
The study aimed to investigate the relationship between laboratory-assessed variables and cross-country marathon mountain biking (XCM-MTB) performance to suggest a more practical approach to monitor performance during the competitive phase. Nine elite athletes performed a battery of tests during the competitive phase of the season, one week before the race. Correlations between the physiological and neuromuscular laboratory-assessed variables and mean race completion time were verified and a multiple regression model was calculated. Cycling economy (r=0.86), power output at the first (POVT1; r=-0.73) and second ventilatory threshold (POVT2; r=-0.94), VO2peak (r=-0.71), peak power output (r=-0.91); peak power (r=-0.80), and mean power (r=-0.85) were very strongly related to race performance. TMG-derivate factors as rectus femoris (r=-0.61) and biceps femoris (r=-0.59) contraction velocity, 30-cm drop jump performance (r=-0.59), mean propulsive power in jump squat at 40% (JS40%; r=-0.65) and 60% (JS60%; r=-0.62) of athlete`s body weight and lower limbs maximal isometric voluntary strength (r=-0.59) were strongly related to race completion time. In an isolated way, the POVT2 explained 87% of race performance. Although both physiological and neuromuscular variables are related to XCM performance, the POVT2 seems to be the main variable during the competitive phase and an easy-to-apply approach should be used to monitor athletes` performance.